Edukasi Kreatif Anak-Anak Melalui Seni Ecoprint Painting Ramah Lingkungan di Desa Senaru, Lombok Utara - Widya Hartati; Sandy Ari Wijaya (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2025)
Senaru Village, Bayan District, North Lombok Regency has abundant natural resources and great potential to be utilized in educational and creative activities. However, the use of natural materials such as leaves and flowers as learning and art media is still very minimal. This community service activity aims to provide environmentally friendly education through ecoprint painting art to children, with a fun, participatory and local potential-based approach. The implementation method includes observation and coordination, socialization of the ecoprint concept, ecoprint practice in groups, to the documentation stage. This activity not only trains children's creativity and motor skills but also fosters concern for the environment and pride in the natural wealth of their village. Through this activity, children are invited to get to know the potential of local flora more closely and appreciate its beauty and usefulness directly. The results of the community service show that ecoprint painting can be an effective education in internalizing environmental conservation values ​​from an early age, while opening up opportunities for the development of sustainable creativity.